AN UNUSUAL CAUSE OF TRAUMATIC BRAIN INJURY IN KHYBER PAKHTUNKHWA: A CASE REPORT - Ali, Mumtaz; Rehman, Zia ur; Usman, Muhammad; Alam, Ikram; Ishaq, Mohammad; Haq, Naeem ul (Journal of Postgraduate Medical Institute, 2012)
Penetrating head injuries can be the result of numerous intentional or unintentional events, including missile wounds, stab wounds, motor vehicle and occupational accidents (nails, iron rods) or assaults (screw-drivers). Penetrating head injuries caused by screw-drivers constitute only a small part of the total number of traumatic head injuries seen in casualty. We report a case of neuro-trauma who was operated in our institution. A 25 years gentleman presented in casualty on with a screw-driver penetrating into the skull, as an unusual case of violence.